2013
DOI: 10.1016/j.bbamem.2012.12.019
|View full text |Cite
|
Sign up to set email alerts
|

The effect of oxidative stress on the membrane dipole potential of human red blood cells

Abstract: The membrane dipole potential (ψ(d)) is an important biophysical determinant of membrane function and a sensitive indicator of lipid organisation. In this study we have used the environmentally sensitive probe di-8-anepps to explore the effects of oxidative stress on the membrane dipole potential of human erythrocytes. Cells suspended in 0.15mM phosphate buffered saline containing 0.1mg/ml albumin maintained a mean value for ψ(d) of 270 (±20) mV over the course of 1hour. In the presence of 0.4mM cumene hydrope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 37 publications
4
27
0
1
Order By: Relevance
“…Previous studies 28 have demonstrated that human red blood cell membranes can be readily labelled with Di-8-ANEPPS. Ratiometric imaging of healthy discotic RBCs indicates that is of the order of 250 mV, varying by around 30 mV along the surface of the cell.…”
Section: Ratiometric Imaging Of Di-8-anepps Labelled Red Blood Cells mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies 28 have demonstrated that human red blood cell membranes can be readily labelled with Di-8-ANEPPS. Ratiometric imaging of healthy discotic RBCs indicates that is of the order of 250 mV, varying by around 30 mV along the surface of the cell.…”
Section: Ratiometric Imaging Of Di-8-anepps Labelled Red Blood Cells mentioning
confidence: 99%
“…The value of differs by 14 % between the two regions of the post-toxin vesicle. This is likely to arise from the change in surface morphology and increase in local curvature in the membrane 28 around the DAG droplet which enables a change in lipid packing as well as changes in spatial organisation of lipid molecules with respect to each other, lipid headgroup configuration and headgroup-associated water.…”
Section: Ratiometric Imaging Of Di-8-anepps-labelled Vesicles Shows Amentioning
confidence: 99%
“…The conformation and properties of Hb were studied by Raman scattering (RS) using inVia confocal Raman microscope (Renishaw, Wotton-under-Edge, UK) [21][22][23][24] with short focus high luminosity monochromator (focal length not more than 250 mm). For excitation of Raman spectra, a laser was used (wavelength of 532 nm, maximum power of 100 mW and 100£ objective).…”
Section: Conformation and Properties Of Hbmentioning
confidence: 99%
“…5). We have previously shown that treatment of RBCs with cumOOH increased both the membrane bending elastic modulus (64) and membrane dipole potential (77), yet these cells are much more resistant to toxin compared with healthy cells, for which higher bending rigidity and dipole potential meant lower resistance to PLY (Fig. 8, A and B, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…This motivated us to investigate whether differences in the membrane physical properties of individual cells within a population of RBCs are correlated with their susceptibility to PLY. We measured the membrane bending elastic modulus (a primary measure of the mechanical compliance of the lipid bilayer (75)), the membrane electrostatic dipole potential (76,77), and the membrane electrostatic surface potential (60, 61) for a number of individual cells within a population of RBCs before toxin exposure. The buffer surrounding the cells was then exchanged with buffer containing toxin, and the time to lysis, i.e.…”
Section: Differences In the Membrane Physical Properties Of Individuamentioning
confidence: 99%